The relevancy of preventive detention in Malaysia - Kamarudin, Abdul Rani; Zainol, Mohd Jamizal (2005)
This paper highlights and discusses human rights from the Islamic viewpoint based on the Quran, the Cairo Declaration of Human Rights in Islam, as well as in the light of the Universal Declaration of Human Rights. It then attepms to give the moral and legal justifications for the use of preventive detention for the sake of public order in society. Thus, this paper specifically discusses preventive detention laws and will deliberate in general the application of Internal Security Act of 1960 (hereinafter referred to as "ISA") in maintaining peace and security in Malaysia. The deliberation will also be focused on other security and public order legislations which also have preventive mechanism as the ISA i.e. Restricted Residence Act 1933 (hereinafter referred to as "RRA"), Prevention of Crime Act 1959 (hereinafter referred to as "PCA"), the Emergency (Public order and Prevention of Crime) Ordinance No. 5 of 1969 (hereinafter referred to as "EPOPOC"), and the Dangerous Drugs (Special Preventive Measures) Act 1985. Other preventive legislations available in other jurisdictions such as India, Northern Ireland, United States and South Africa will also be highlighted to foster the indispensability of preventive detention in ensuring 'harmony' in the society. This paper will ultimately deduce whether preventive legislation is allowed in Islamic law.